The association between overall health, psychological distress, and occupational heat stress among a large national cohort of 40,913 Thai workers - Benjawan Tawatsupa; Lynette L-Y. Lim; Tord Kjellstrom; Sam-ang Seubsman; Adrian Sleigh; The Thai Cohort Study teama (Taylor & Francis Group, 2010)
Background: Occupational heat stress is a well-known problem, particularly in tropical countries, affecting workers, health and well-being. There are very few recent studies that have reported on the effect of heat stress on mental health, or overall health in workers, although socioeconomic development and rapid urbanization in tropical developing countries like Thailand create working conditions in which heat stress is likely. Objective: This study is aimed at identifying the relationship between self-reported heat stress and psychological distress, and overall health status in Thai workers. Results: 18% of our large national cohort (>40,000 subjects) often works under heat stress conditions and males are exposed to heat stress more often than females. Furthermore, working under heat stress conditions is associated with both worse overall health and psychological distress (adjusted odds ratios ranging from 1.49 to 1.84). Conclusions: This association between occupational heat stress and worse health needs more public health attention and further development on occupational health interventions as climate change increases Thailand's temperatures.